Buying Teachers: Neoliberalism, Salary Supplements,and Teacher Resistance Practices in Andalusia - Maximiliano Ritacco Real; Miguel Martínez Rodríguez (Universidad Autónoma de Baja California, 2021)
This article examines howteachers in the public education system in Andalusia (Spain) perceive the neoliberal logic of salary supplements. It seeks to capture the perspectives of teaching staff (through 30 in-depth interviews) with respect to a business management practice in public education aimed at "improving" academic outcomes. The study employs a qualitative interpretive methodology and applies content analysis and grounded theory. Data was analyzed with NVivo 8 software. The results present teachers' arguments for accepting and/or rejecting salary supplements and highlight the spread of new neoliberal political and cultural engineering in Andalusian education and teachers' resistance to these processes.